A Comparative Study of Drospirenone and Desogestrel: An Overview of Benefi ts and Side Effects - Bhattacharya, Pamamita; Kapoor, Nandini; Kyal, Amit; Mukhopadhyay, Partha (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aims: To study the antiandrogenic and antimineralocorticoid activity of drospirenone, a novel progestogen used as a component of combined oral contraceptive pill (COC) and compare it’s clinical and biochemical effects with that of desogestrel, the most commonly used progestogenic component of COC. Methods Study design: prospective analytical study. Population and setting: study was conducted in our department from July 2008 to June 2010. Two hundred women were randomly allocated into two groups. First group received combination of 3mg drospirenone and 30 mcg ethinyl estradiol (DRSP/EE) and the other group was given COC containing 150mcg desogestrel and 30 mcg ethinyl estradiol (other OCP group). Results: The DRSP/EE group showed no significant decrease in body weight, Ferriman gallwey Score (FG), systolic and diastolic blood pressure. No evidence of sodium retention seen in any patients. 86% women had decrease in serum sodium from baseline. There was significant increase in HDL-Cholesterol level by 7.52% and no significant decrease in LDL-Cholesterol level. In the other OCP group, 52 subjects had increase in body weight, 30% showed increase in FG score and none had any decrease in blood pressure. 62% women had net gain in serum sodium level. Serum Triglyceride, HDL-Cholesterol, LDL-Cholesterol all were increased. Conclusion: DRSP/EE combination is well tolerated, demonstrating good cycle control and a beneficial effect on skin condition. It exerts significant antiandrogenic activity and is effective in improving hirsutism. It also has positive effect on serum electrolyte composition and lipid profile. Keywords: Combined oral contraceptives, drospirenone, desogestrel DOI: http://dx.doi.org/10.3126/njog.v6i1.5247 NJOG 2011; 6(1): 17-21